FX11 limits Mycobacterium tuberculosis growth and potentiates bactericidal activity of isoniazid through host-directed activity - Gopinath Krishnamoorthy; Peggy Kaiser; Ulrike Abu Abed; January Weiner; Pedro Moura-Alves; Volker Brinkmann; Stefan H. E. Kaufmann (The Company of Biologists, 2020)
Lactate dehydrogenase A (LDHA) mediates interconversion of pyruvate and lactate, and increased lactate turnover is exhibited by malignant and infected immune cells. Hypoxic lung granuloma in Mycobacterium tuberculosis-infected animals present elevated levels of Ldha and lactate. Such alterations in the metabolic milieu could influence the outcome of host-M. tuberculosis interactions. Given the central role of LDHA for tumorigenicity, targeting lactate metabolism is a promising approach for cancer therapy. Here, we sought to determine the importance of LDHA for tuberculosis (TB) disease progression and its potential as a target for host-directed therapy. To this end, we orally administered FX11, a known small-molecule NADH-competitive LDHA inhibitor, to M. tuberculosis-infected C57BL/6J mice and Nos2−/− mice with hypoxic necrotizing lung TB lesions. FX11 did not inhibit M. tuberculosis growth in aerobic/hypoxic liquid culture, but modestly reduced the pulmonary bacterial burden in C57BL/6J mice. Intriguingly, FX11 administration limited M. tuberculosis replication and onset of necrotic lung lesions in Nos2−/− mice. In this model, isoniazid (INH) monotherapy has been known to exhibit biphasic killing kinetics owing to the probable selection of an INH-tolerant bacterial subpopulation. However, adjunct FX11 treatment corrected this adverse effect and resulted in sustained bactericidal activity of INH against M. tuberculosis. As a limitation, LDHA inhibition as an underlying cause of FX11-mediated effect could not be established as the on-target effect of FX11 in vivo was unconfirmed. Nevertheless, this proof-of-concept study encourages further investigation on the underlying mechanisms of LDHA inhibition and its significance in TB pathogenesis.